Romania : Public Expenditure and Institutional Review : Background Papers - World Bank (World Bank, 2012)
The government has embarked upon a comprehensive and difficult medium term program for reforming the public sector aimed at rebalancing the relation between revenue and spending and enhancing the efficiency and efficacy of service delivery. The Romanian economy has been hit hard by the global economic downturn. Latest estimates suggest that real Gross Domestic Product (GDP) may have contracted by around 7 percent in 2009, before modestly recovering in 2010. The severe decline in output has had a significant adverse effect on consolidated budget revenues, which fell substantially below the initial target in 2009. To prevent a further deterioration of the already large fiscal deficit, the shortfall in revenue has led to adjustments in spending. Consolidation of expenditure needs however continue in order to put public finances on a sustainable trajectory over the medium term. The report is structured in two volumes. The first volume synthesizes the menu of options suggested to reduce the short term gap between budget expenditure and revenues. It also highlights the key challenges and recommendations for improving efficiency and efficacy of spending in the sectors investigated. Volume two consists of the background analyses, with individual chapters dedicated to the fiscal framework; public pay; pensions; education; health; and agriculture. The report makes the case that, in the current crisis environment and consistent with experience worldwide, the gap between expenditure and revenue should be done primarily by reducing the level of current spending.